2016
DOI: 10.1007/s00432-016-2115-6
|View full text |Cite
|
Sign up to set email alerts
|

Partial liver resection results in a significantly better long-term survival than locally ablative procedures even in elderly patients

Abstract: In patients aged 70 years and over, long-term prognosis is independently influenced by CLIP score and treatment procedure and other findings have only minor influence on long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In the comparison of RFA and surgical resection by postoperative outcomes, contradictory results were yielded. Peng et al[73] reported that patients having RFA had better outcomes than those having surgical resection, while Bauschke et al[74] and Yu et al[75] reported better outcomes for surgical resection. Another retrospective study by Jiang et al[76] concluded that RFA should be recommended for elderly patients (age > 65 years) with HCCs ≤ 20 mm while surgical resection would be a better treatment for HCCs of 21-50 mm in elderly patients.…”
Section: Radiofrequency Ablationmentioning
confidence: 99%
“…In the comparison of RFA and surgical resection by postoperative outcomes, contradictory results were yielded. Peng et al[73] reported that patients having RFA had better outcomes than those having surgical resection, while Bauschke et al[74] and Yu et al[75] reported better outcomes for surgical resection. Another retrospective study by Jiang et al[76] concluded that RFA should be recommended for elderly patients (age > 65 years) with HCCs ≤ 20 mm while surgical resection would be a better treatment for HCCs of 21-50 mm in elderly patients.…”
Section: Radiofrequency Ablationmentioning
confidence: 99%
“…demonstrated that SR ( n = 63) resulted in significantly better long-term survival rates than RFA ( n = 64) in elderly patients (≥70 years) with early-stage HCC ( P < 0.05). [ 12 ] The controversy between the two studies is obvious, as are their limitations, such as small sample size, selection bias, lack of histological diagnosis, or subgroup analyses. Therefore, this large population-based retrospective study was conducted using PSM analysis to compare the different survival outcomes of SR ( n = 461) and RFA ( n = 575) in elderly patients (≥65 years) with single HCC ≤5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Hence, for elderly patients with early-stage HCC who are candidates for both SR and RFA, it remains controversial which treatment provides better long-term survival outcomes. [ 12 13 ] We therefore compared the survival benefits of SR with those of RFA as the first-line treatment in elderly patients (≥65 years) with single HCC ≤5 cm using Surveillance, Epidemiology, and End Results (SEER), a large population-based database.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 3 ] However, SR may provide a greater long-term survival benefit compared to RFA among HCC patients. [ 4 ]…”
mentioning
confidence: 99%
“…Despite the study limitations which include study design, missing data such as the Child-Pugh score, performance status, patients' comorbidities, tumor characteristics, and location, it has a reasonable sample size and is consistent with what has been published in the literature regarding the safety and efficacy of RFA and SR group in elderly HCC patients. [ 4 6 ] However, more high-quality studies are required to validate the result. Yet, research such as this helps to inform multidisciplinary patient-centered decision making to personalize treatment based on liver dysfunction, tumor size, tumor number, comorbidities, and performance status.…”
mentioning
confidence: 99%